Overlooked mammal diversity and conservation priorities in Italy: Impacts of taxonomic neglect on a Biodiversity Hotspot in Europe - Gippoliti, Spartaco; Groves, Colin P. (Zootaxa, 2018)
For more than half a century, little taxonomic revisionary work has been directed towards extant European mammals so that the limits of most geographically widespread polytypic species remained scientifically untested. Occasionally, taxonomic changes have been proposed and several new species have been resurrected / discovered in the last decades mainly on the basis of genetic studies, often considered the only tool to establish objective species boundaries. Nevertheless, the precise details of species boundaries, subspecific variation and phylogenetic relationships remain unknown for several European mammal taxa. The inadequacies of outdated, incomplete taxonomic knowledge reach an extreme in southern Europe, and notably Italy, where cryptic species abound and specimen-based research is scanty. The state of mammalian taxonomic knowledge in Italy shows that Linnaean and Wallacean shortfalls are no means restricted to hyperdiverse, understudied tropics. They undermine our knowledge of temperate regions, with severe consequences for biodiversity conservation policies in Europe, where conservation assessments overlook significant endemic biodiversity. European mammalogy stands to benefit from an infusion of the tree-thinking philosophy that undergirds evolutionary theory and particularly phylogenetic methods systematics. Furthermore, it is important that taxonomic research be seen as a normal part of scientific advancement and of critical importance as the basis of a sound biodiversity conservation policy.